A Urologist’s Perspective: Initial Experiences With SpaceOAR Hydrogel Insertion for Prostate Cancer Patients - Hyunho Han; Ik Jae Lee; Woong Sub Koom; Chan Woo Wee; Woong Kyu Han (Journal of Urologic Oncology)
Purpose To evaluate the placement accuracy and learning curve of SpaceOAR hydrogel and gold fiducial marker insertion in Korean prostate cancer patients undergoing carbon ion radiotherapy (CIRT), performed by a single urologist without prior experience. Materials and Methods In this retrospective observational study, 104 prostate cancer patients scheduled for CIRT at Severance Hospital between November 2022 and October 2023 underwent simultaneous SpaceOAR hydrogel insertion and 2 gold fiducial markers placement under transrectal ultrasound guidance. Postprocedural magnetic resonance imaging scans assessed spacer placement accuracy using the SpaceOAR Symmetry Score. Complications were documented and graded according to the Common Terminology Criteria for Adverse Events v5.0. Statistical analyses evaluated the impact of age, prostate volume, and operative time on complication rates and procedural efficiency. Results Spacer placement was successful in all cases, achieving SpaceOAR Symmetry Score of 2.0 or less in 85.58% of the cases. The average operative time for the first 50 cases was 12.70±3.40 minutes, while for the latter 54 cases was 12.50±5.35 minutes, which suggests no significant learnig curve exist. Complications occurred in 25 of patients (24.0%), with constipation (9.6%), weak urinary stream (4.8%) and perianal pain (3.8%) being the most common. Acute urinary retention (grade 2) occurred in 3 patients and was not related to patient age or the presence of benign prostatic hyperplasia. Other complications were rare and mostly mild (grade 1). Conclusions SpaceOAR hydrogel insertion with gold fiducial marker placement is a reliable and efficient procedure that can be effectively performed by urologists without prior experience in patients undergoing CIRT. The procedure demonstrates a significant learning curve, with operative efficiency improving over time, supporting its feasibility and potential for widespread adoption.